2019
DOI: 10.20469/ijbas.5.10004-4
|View full text |Cite
|
Sign up to set email alerts
|

The Pathway to Improve Innovation Capacity for Lao Firms: The Roles of Transformational Leadership and Psychological Resources of Employees

Abstract: Innovation is the key and fundamental forces for firms to survive and grow in a competitive environment. The paper aims to examine the correlation between Transformational Leadership (TL) and employees' psychological sources and how they affect an organization's Innovation Capability (IC). Structural Equations Modeling (SEM) is utilized to elaborate the relationship among the proposal factors using survey data gathered from 315 participants of 65 medium and small-sized firms in Vientiane, Laos. The findings sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 60 publications
0
17
0
2
Order By: Relevance
“…Bass (1999) defined transformational leadership (TL) with four characteristics including (1) idealized influence: ability to provide a vision and perception of mission, instilling pride, gaining respect and trust); (2) intellectual stimulation: ability to promote intelligence, rationality and attentive problem solving); (3) inspirational motivation: interested in communicating high expectations, using symbols to focus efforts, expressing important purposes in simple ways); and (4) individualized consideration: interested in personal attention, treating each employee individually, coaching and advising. The theory of TL has attracted much observation from scholars and emerged as one of the most powerful leadership theories (Le & Lei, 2017;Le & Lei., 2018a,b,c;Van et al, 2018;Hui et al, 2018;Le et al, 2018a,b;Phong et al, 2018;Lei et al, 2019a,b,c,d;Sengphet et al, 2019;Le & Tran, 2019;Ha et al, 2019). Consequently, investigating the relationship between TL and innovation capability of Vietnamese firms will enrich the understanding and knowledge of new leadership style and innovation management in Vietnamese context.…”
Section: Innovation Capabilitymentioning
confidence: 99%
“…Bass (1999) defined transformational leadership (TL) with four characteristics including (1) idealized influence: ability to provide a vision and perception of mission, instilling pride, gaining respect and trust); (2) intellectual stimulation: ability to promote intelligence, rationality and attentive problem solving); (3) inspirational motivation: interested in communicating high expectations, using symbols to focus efforts, expressing important purposes in simple ways); and (4) individualized consideration: interested in personal attention, treating each employee individually, coaching and advising. The theory of TL has attracted much observation from scholars and emerged as one of the most powerful leadership theories (Le & Lei, 2017;Le & Lei., 2018a,b,c;Van et al, 2018;Hui et al, 2018;Le et al, 2018a,b;Phong et al, 2018;Lei et al, 2019a,b,c,d;Sengphet et al, 2019;Le & Tran, 2019;Ha et al, 2019). Consequently, investigating the relationship between TL and innovation capability of Vietnamese firms will enrich the understanding and knowledge of new leadership style and innovation management in Vietnamese context.…”
Section: Innovation Capabilitymentioning
confidence: 99%
“…Thus, a better evaluation of job content and job context by the employees leads to a sense of obligation and commitment toward the organization (Ahmad, 2018). Leaders can develop positive employee morale by redesigning and enriching jobs (Liu et al, 2013;Sengphet et al, 2019). Knowing these attributes of job characteristics theory, the leaders can use this information for work with the subordinates to ensure their job satisfaction is intact and positive that can lead them to feel embedded toward their job and organization.…”
Section: Moderating Impact Of Job Characteristics In the Relationship Between Transformational Leadership And Job Embeddednessmentioning
confidence: 99%
“…Scholars recognized that innovation capability of firms allows them to adapt effectively with the lack of certainty of both external and internal environment, and bring firms the success in the dynamic markets in long term Yang et al, 2018;Lei et al, 2019). In the context of small and medium enterprises (SMEs), prior studies indicated that because SMEs are limited resources, their innovation capability becomes very important to compete successfully in the marketplace (Sengphet et al, 2019). However, it is not easy for SMEs to develop it properly due to lack of understanding on antecedents of innovation Sengphet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of small and medium enterprises (SMEs), prior studies indicated that because SMEs are limited resources, their innovation capability becomes very important to compete successfully in the marketplace (Sengphet et al, 2019). However, it is not easy for SMEs to develop it properly due to lack of understanding on antecedents of innovation Sengphet et al, 2019). To fill the theoretical gaps, this study will clarify the influence of transformational leadership (TL) on innovation capability of SMEs via the mediating role of knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%